New Structured Dairy Products Based on Quality Complaints and Risk Qualimetry - Valentina S. Yankovskaya; Nina I. Dunchenko; Kermen V. Mikhaylova (Техника и технология пищевых производств)
Successful food production business depends on how well entrepreneurs identify, assess, and take into account various risks, including technological, at the stage of product design. The analysis of quality complaints and consumer opinions is vital for product design or improvement. The research objective was to develop structured dairy products based on the quality complaint analysis and risk qualimetry. The research featured quality complaints and factors that affect the quality of structured dairy products. It involved the methodology of the technological risk qualimetry and generally accepted control tools and quality assessment methods. Popular structured dairy products were identified and tested for the weight coefficients of their consumer properties and technological risks. The analysis covered five years of quality complaints and made it possible to identify and rank the reasons behind nonconforming structured dairy products. Matrix diagrams helped to forecast various factors, e.g. those based on raw materials or formulation, technological, organizational, etc. The diagrams reflected the degree of factor influence onthe identified risks. The research established control coefficients of each risk, as well as the importance of each factor as a risk management tool. The article introduces several risk management tools related to nonconforming products and aimed at improving consumer properties at the design stage. It also features the formulation of a new structured curd product with production technology and technical documentation. The proposed approach to the development of structured dairy products is based on risk qualimetry and takes into account quality complaints. It provides a prompt formulation assessment, guarantees high consumer properties, and minimizes the risks of producing nonconforming products.